Carbon demand drives microbial mineralization of organic phosphorus during the early stage of soil development - Wang, Jipeng; Wu, Yanhong; Zhou, Jun; Bing, Haijian; Sun, Hongyang (Biology and fertility of soils, 2016)
Despite that organic phosphorus (Po) is a source of bioavailable P during the early stage of soil development, it remains unclear whether P availability or organic carbon (C) mineralization is the main regulator of Po mineralization. In this study, the P availability (labile inorganic P, Pi) and the potential organic C mineralization (β-glucosidase activity) were investigated at the Hailuogou Chronosequence and a reference site (35–125 and ∼1400 years after glacier retreat, respectively) to decipher their relationships with the potential Po mineralization (acid and alkaline phosphomonoesterase activities). Labile Pi displayed no trend in the soil profile, whereas it was significantly higher at the reference site than the young sites. Enzyme activities decreased down the soil profile, but this trend weakened for specific activities (enzyme activity per microbial biomass C). Enzyme activities and specific activities displayed no trend with the succession stage. Potential Po mineralization was more related to potential organic C mineralization ( R 2 = 0.41–0.69, p < 0.0001) than P availability ( R 2 = 0.05–0.09, p ≤ 0.05). By increasing the specific activity of β-glucosidase, the microbial biomass C:P ratio decreased to reach the value of 8:1. Probably, the phosphate in the excess of microbial demand was released as the by-product of C mineralization. At the young sites of the chronosequence, the significant correlation between Po and C concentrations in the surface mineral horizon ( R 2 = 0.85, p < 0.0001) suggested that the mineralizations of Po and organic C were linked to each other. The results suggested that the demand for C may drive the microbial mineralization of soil Po during the early stage of soil development, and the phosphate released by the Po mineralization may serve as a potential source of labile Pi for plants.